La mosca blanca Bemisia tabaci (Gennadius) como plaga y vectora de virus en frijol común (Phaseolus vulgaris L.) - Cuéllar Jimenez, M.E.; Morales Garzón, Francisco José (2006)
The whitefly Bemisia tabaci is one of the most widely distributed pests found in tropical and subtropical agricultural regions of the world, where it affects over 600 different cultivated and wild plant species. The damage it causes is due to diverse effects of the insect on the attacked plant, such as weakening the plant through extraction of nutrients; physiological disorders induced by biotype B of B. tabaci (e.g. irregular ripening of tomato and silver leaf of cucurbits); excretion of honeydew that promotes the growth of fungi on the plant ( i.e. sooty molds); and the transmission of begomoviruses (Geminiviridae). In common bean, bean golden mosaic and bean golden yellow mosaic begomoviruses are the two most widely distributed pathogens in Latin America, where they cause yield losses of up to 100%. In Colombia, the arrival of biotype B of B. tabaci and the occurrence of climatic changes favorable for the development of high populations of the insect, have coincided in recent years with begomovirus outbreaks in crops such as tomato and snap bean. The most efficient control strategy for begomovirus is the use of resistant varieties. Unfortunately, adequate breeding programs for controlling new outbreaks of begomovirus in Colombia do not exist. This situation, plus the lack of proper technical assistance, has led farmers to rely almost exclusively on the application of insecticides to combat whiteflies. This review summarizes the information available on the main begomoviruses of common bean reported in Latin America, including those viruses recently detected in Colombia, and the control measures available.